Coca-colonization and the Cold War : the cultural mission of the United States in Austria after the Second World War - Wagnleitner, Reinhold, 1949- (University of North Carolina Press, 1994)
"Reinhold Wagnleitner argues that cultural propaganda played an enormous part in integrating Austrians and other Europeans into the American sphere during the Cold War ... Wagnleitner traces the intimate relationship between the political and economic reconstruction of a democratic Austria and the parallel process of cultural assimilation. Initially, U.S. cultural programs had been developed to impress Europeans with the achievements of American high culture. However, popular culture was more readily accepted, at least among the young, who were the primary target group of the propaganda campaign. The prevalence of Coca-Cola and rock 'n' roll are just two examples addressed by Wagnleitner. Soon, the cultural hegemony of the United States became visible in nearly all quarters of Austrian life: the press, advertising, comics, literature, education, radio, music, theater, and fashion. Hollywood proved particularly effective in spreading American cultural ideals"--Publisher's description